Spider silk as an active scaffold in the assembly of gold nanoparticles and application of the gold-silk bioconjugate in vapor sensing - Singh, Amit; Hede, Shantesh; Sastry, Murali (Small, 2007)
Spider silk is being viewed with interest by materials scientists due to its excellent resilience and mechanical properties. In this paper we show that spider silk is an excellent scaffold for the one-step synthesis and assembly of gold nanoparticles. Formation of a gold nanoparticle-spider-silk bioconjugate material is accomplished by simple reaction of the fibers with aqueous chloroauric acid. The gold nanoparticles thus formed are strongly bound to the spider-silk fiber surface enabling study of the electrical properties of the nano bioconjugate. Using the well-known contraction/expansion behavior of the fibers in solvents of varying polarity, we show that exposure of the gold nanoparticle-spider silk bioconjugate to vapors of methanol and chloroform leads to changes in electrical transport through the nanoparticles and thus, the possibility of developing a vapor sensor. The bioconjugate shows excellent response time and cycling efficiency to methanol vapors. The activation energy of electron transport from one gold nanoparticle to another in the nanobiocojugate was determined from temperature-dependent electron-transport measurements to be approximately 1.7 eV.
Keywords: bioconjugates; Gold; Nanoparticles; sensors; spider silk